An accelerated malting procedure – influences on malt quality and cost savings by reduced energy consumption and malting losses. Issue 2 (April 2015) - Müller, Christian; Methner, Frank‐Jürgen
Abstract : In times of rapidly increasing energy costs and rising importance of economic efficiency, the malting industry is searching for possibilities to reduce malting time to lower their production costs and to increase production capacities. The aim of this study was to compare a step‐wise optimized accelerated malting procedure, combining optimal parameters found in previous individual investigations about steeping, germination and withering with two reference malting programmes: a standard laboratory malting programme according to MEBAK and a programme applied in an industrial malting plant. For five investigated spring barley cultivars, sufficient malt qualities according to the MEBAK specifications could be achieved in a malting process that was about 2 days shorter. Despite slightly lower extract contents, resulting from slightly higher pH values and activities of the starch degrading α ‐ and β ‐amylases, a reduced and thus improved proteolytic modification, improved malt homogeneities, a reduced thermal impact resulting in lower malt colours, in turn implying an increased oxidative flavour stability, and an improved behaviour of premature yeast flocculation could be observed when malting was accelerated. The lautering properties, cytolytic modifications, deoxynivalenol content and gushing potential were not influenced in a significant positive or negative way. Next to the notable production time reduction, decreased dimethyl sulphide precursor contents imply advantages for the brewing and malting industry with regard to a shorter necessary boiling and kilning time. Further significant cost savings of €1.27–4.87/t malt could be calculated owing to a reduction in the amount of electrical energy used for aerating and cooling during germination and lower malting losses, depending on the cultivar. Copyright © 2015 The Institute of Brewing & Distilling